Diversidade genética de três estoques de piapara (Leporinus elongatus), utilizando RAPD - Gomes, Patrícia Cristina (2007)
Recently the Brazilian aquiculture production has presented a great progress. Amongst cultivated native species in Brazil, piapara (Leporinus elogatus) has been widely praised. With the objective of to evaluate restock programs, the variability and genetic divergence of three piapara supplies had been analyzed, using RAPD technique. The first supply belongs to the Aquiculture and Hydrology Station of Duke Energy International (A); second to the Rolândia fish culture (B) and third to the Restock Program of Paraná Rivers (C). Ten primers used for RAPD produced 105 polymorphic loci, conferring a polymorphism of 98.1% for the three evaluated supplies. Polymorphism loci percentage and Shannon index were higher for a supply. However, all values were high, indicating high intrapopulation diversity. The Gst values indicate a low genetic variation between A x B stocking and a moderate differentiation amongst others. The Nm was higher between A x B supplies. Genetic distance and dendrogram, indicate that A x B supplies are less distant genetically.